Hubungan Faktor Internal dan Eksternal Bidan dalam Pelayanan Antenatal di Puskesmas Kota Padang - Silvia Adi Putri (Maternal Child Health Care, 2022)
The success of maternal health efforts can be seen from the indicators of maternal mortality rate - The number of maternal deaths increases from 17 people in 2015 to 20 people by 2016. To reduce maternal mortality, optimal antenatal care is needed. The purpose of this study is to see the relationship between internal and external factors of midwives with antenatal care in community health centers of Padang city in 2017.This research is of quantitative type with cross sectional study desig. Population in this research includes all midwife who served in maternity wards at community health centers of Padang city, amounting to 40 people. The sampling technique used herein is total sampling. Data collection was conducted in November 2015 until January 2016. Data analysis are univariate, bivariate and multivariate.According to the results of the study, more than half of the respondents have provided antenatal care up to standards, were never professionaly trained, were nice, had been working for long enough, lacking boss commitment, were not well-received by their work environment, and half of respondents have good motivation. There is a correlation between the midwife’s attitudes, motivation, boss commitment and environmental acceptance with antenatal care, and no correlation between education, training, and length of service with antenatal care.It is concluded that internal factors related to antenatal care are attitudes, motivation, external factors related to antenatal care, boss commitment and environmental acceptance. Community health center leaders are advised to truly commit to the implementation of antenatal care, while midwives are advised to adopt good behavior and motivation in implementing antenatal care according to the applicable standards. Keywords: Internal Factor, External Factor and Antenatal Care